2020
DOI: 10.33403/rigeo.791713
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Inquiry-Based Education in Geography Teaching – Findings about Teachers´Attitudes

Abstract: Young people's interest in scientific and technical subjects, including geography, has been declining for a long time.According to the European Commission, the most important reason for the decline in interest is the way these subjects are taught in primary and secondary schools. As a result, numerous projects to support inquiry-based methods have been launched in recent years and significant changes have been made to the national curriculum in many of the European countries. Geography as a school subject, due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Thus, inquiry learning began to be developed in national curriculum and it turned out that this had a significantly good impact. Geography as a multidisciplinary study provides options for designing more interesting learning and can increase motivation by using inquiry learning [28]. In the application of the SIHyL model, it is effective to familiarize students with map reading activities during the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inquiry learning began to be developed in national curriculum and it turned out that this had a significantly good impact. Geography as a multidisciplinary study provides options for designing more interesting learning and can increase motivation by using inquiry learning [28]. In the application of the SIHyL model, it is effective to familiarize students with map reading activities during the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Also, geography is considered as an active discipline, and creativity is at its core (Catling, 2005 ; Hintermann et al, 2020 ). In addition, other researchers have revealed that students with higher creativity perform better in inquiry-based learning in geography (Walkington et al, 2011 ; Tomčíková, 2020 ). On the basis of these arguments, we formulate the following hypothesis:…”
Section: Theoretical Basis and Hypothesismentioning
confidence: 97%